Assistance for post-natal cupping massage according to the Sunnah of the Prophet - Machfudloh Machfudloh; Muliatul Jannah; Yuli Astuti (Community Empowerment, 2022)
Postnatal refers to the time frame starting 6 to 8 weeks following the birth. The uterus, lochia, vagina, and vulva are among the physical changes that postpartum women experience. The uterus will gradually return to its pre-pregnancy state during the puerperium. However, there are a number of issues like bleeding, pain, and stress during this time of transformation. The purpose of this service is to improve postpartum mothers' understanding of postpartum difficulties and their abilities to avoid problems through postnatal cupping massage. A question-and-answer lecture, a demonstration, and practice are the techniques used. The outcome of this training is a better understanding of issues affecting postpartum mothers as well as improved cupping massage techniques. For postpartum mothers, this activity is a great way to gain more understanding and information about the postpartum period and to identify other postpartum mothers who are knowledgeable and sensitive to all physical and psychological complaints. This will help them get through the postpartum period without any discomfort.